Mathematical Modeling of Flow and Particle Distribution in Newly-Designed Multicyclones - Djurayev Sherzod Sobirjonovich (Scientific Trends, 2025)
A comprehensive mathematical model is proposed for a multicyclone separator equipped with a spiral offset inlet and multi-core guide vanes. The model couples the incompressible Navier–Stokes equations—solved in cylindrical coordinates—with a Lagrangian discrete-phase formulation for particle motion. A Reynolds-averaged RNG k–ε closure is adopted for the carrier gas, whereas particles with diameters from 1 μm to 20 μm are tracked through a one-way-coupled discrete-phase model. Grid-independence, second-order spatial discretisation, and time-accurate integration ensure numerical robustness. CFD predictions are validated against 1:5-scale laboratory measurements obtained by particle-image velocimetry and laser diffraction analysis. Results show a 12 % increase in axial-core velocity and a 10–12 % improvement in sub-5-μm collection efficiency relative to a conventional design, while pressure loss rises by only 4 %.
Keywords: Multicyclone; CFD; particle separation; axial velocity profile; RNG k–ε; mesh independence; guide vane design.